Long-term incentives and financial performance: a study of real estate investment trusts listed on the Johannesburg Stock Exchange - Mbhokota, Lunghile (The IIE, 2024)
In line with global benchmarks of digitisation, the judiciary in South Africa decided to implement the CaseLines Document Management System in January 2020. This coincided shortly after with the COVID-19 pandemic, which forced digitisation anyway. The concept of digitising court and legal records would prove efficient regarding process and time. Therefore, the purpose of this study was to investigate stakeholders’ perceptions of the usability of CaseLines Document Management System. By understanding the perceptions of the users, the researcher wanted to establish efficiencies and gaps in using the CaseLines Document Management System. A qualitative study was undertaken, and twenty participants from one legal practice in Pretoria were proposed. After all ethical considerations were followed, a semi- structured interview guide was used to collect data. Ten interviews were conducted, and saturation was reached at eight participants. Atlas ti software was used to analyse the transcribed interviews. The data was categorised thematically. The key finding of the study is that legal practitioners have two-fold perceptions on the usability of CaseLines system: one view arguing for efficiency and the other for inefficiency of the system. The study also found that little to no formal training was applied for users of CaseLines Document Management System. Users self-taught using online resources. There wasa mixed response on the saving of time and the allocation of court dates. Future research is recommended on users in the courts and a broader geographic reach.
Keywords: Agency theory; Corporate governance; Long term incentives; Financial performance; Real estate investment trusts